Effect of mammalian target of rapamycin inhibitors on cytomegalovirus infection in kidney transplant recipients receiving polyclonal antilymphocyte globulins: a propensity score‐matching analysis. (26th September 2016) - Cervera, Carlos; Cofan, Frederic; Hernandez, Cristina; Soy, Dolors; Marcos, Maria Angeles; Sanclemente, Gemma; Bodro, Marta; Moreno, Asunción; Diekmann, Fritz; Campistol, Josep Maria; Oppenheimer, Frederic
Summary: Mammalian target of rapamycin inhibitors (mTORi) prevents cytomegalovirus (CMV) infection in kidney transplant (KT) patients. From May 2010 to December 2013, all KT recipients were retrospectively analysed. Maintenance immunosuppression regimen was divided into mTORi or calcineurin inhibitors (CNI)‐based regimen. Since June 2011, CMV‐seropositive recipients (R+) treated with high‐intensity immunosuppression and mTORi did not receive anti‐CMV prophylaxis. We analysed 350 consecutive patients, of which 95 (27%) received mTORi and 255 (73%) CNI‐based immunosuppression. A Cox‐regression multivariate analysis showed that the use of mTORi‐based immunosuppression during all follow‐up reduced the risk of CMV infection (HR 0.36, 95% CI 0.15–0.89, P = 0.028) and confirmed in a propensity score‐matched cohort (HR 0.4, 95% CI 0.1–0.9, P = 0.047). Early discontinuation of mTORi increased the risk of CMV infection (HR 3.2; 95% CI 1.7–6.0) in univariate analysis. The incidence of CMV infection was not higher among CMV R+ patients on mTORi and requiring high‐intensity immunosuppression when CMV prophylaxis was not given. The use of mTORi protected for CMV infection in KT patients, allowing to avoid antiviral prophylaxis for R+ patients receiving high‐intensity immunosuppression. The increased risk of CMV infection after early discontinuation of mTORi warrants further research.